APLIKASI TRANSLITERASI BAHASA SUNDA THE APPLICATION OF SUNDANESE LANGUAGE TRANSLITERATION - Dini Pujiatin; Uning Lestari; Erma Susanti (Jurnal SCRIPT, 2018)
Regional language is a language spoken in an area within a country of nationality, whether it's on a small area of federal, State or provincial, or a wider area. One of them in the Sundanese of West Java area. Sundanese language is no longer the mother tongue/first language in its own area, but it's been made into a second language after English. Sundanese language transliteration applications are expected to preserve the Sundanese language as one of the regional language in Indonesia. Sundanese Language Transliteration applications created with the PHP programming language and the design of the program is created by using the Unified Modeling Language (UML). The database used in Sundanese language transliteration application is MySQL. Sublime Text Editor program uses 3. Application of transliteration of the Sundanese language has 2 levels of users, i.e. admin and visitors. Admin on duty to manage the words that will be transliterasikan, while the general public visitor is using this application. The process of transliteration can be made from Indonesia to the Sundanese language Sundanese language smooth and rough, from the subtle to the Sundanese language Sundanese Indonesia and coarse, and from rough to the Sundanese language Sundanese and Indonesian. Web applications are so that you can access from a laptop's browser without having to install the program. The application is also able to provide appropriate display type of browser to access it, for example if the access via smartphone, then the look of the application that appears is the display of the mobile version.